Experience of Playing Sport or Exercising for Women with Pelvic Floor Symptoms: A Qualitative Study - Jodie G. Dakic; Jean Hay-Smith; Kuan-Yin Lin; Jill Cook; Helena C. Frawley (SpringerOpen, 2023)
Abstract Background Women participate in sport at lower rates than men, and face unique challenges to participation. One in three women across all sports experience pelvic floor (PF) symptoms such as urinary incontinence during training/competition. There is a dearth of qualitative literature on women's experiences of playing sport/exercising with PF symptoms. The purpose of this study was to explore the lived experience of symptomatic women within sports/exercise settings and the impact of PF symptoms on sports/exercise participation using in-depth semi-structured interviews. Results Twenty-three women (age 26-61 years) who had experienced a breadth of PF symptom type, severity and bother during sport/exercise participated in one-one interviews. Women played a variety of sports and levels of participation. Qualitative content analysis was applied leading to identification of four main themes: (1) I can't exercise the way I would like to (2) it affects my emotional and social well-being, (3) where I exercise affects my experience and (4) there is so much planning to be able to exercise. Women reported extensive impact on their ability to participate in their preferred type, intensity and frequency of exercise. Women experienced judgement from others, anger, fear of symptoms becoming known and isolation from teams/group exercise settings as a consequence of symptoms. Meticulous and restrictive coping strategies were needed to limit symptom provocation during exercise, including limiting fluid intake and careful consideration of clothing/containment options. Conclusion Experiencing PF symptoms during sport/exercise caused considerable limitation to participation. Generation of negative emotions and pain-staking coping strategies to avoid symptoms, limited the social and mental health benefits typically associated with sport/exercise in symptomatic women. The culture of the sporting environment influenced whether women continued or ceased exercising. In order to promote women's participation in sport, co-designed strategies for (1) screening and management of PF symptoms and (2) promotion of a supportive and inclusive culture within sports/exercise settings are needed.